Altered shear stress of blood flow causes plasma membrane damage in endothelial cells - Nikita Raj; Chang Pan; Ann Marleen Starke; Anna L. L. Matos; Oliver Soehnlein; Volker Gerke (Blood Vessels, Thrombosis & Hemostasis)
Abstract: The endothelial lining of blood vessels faces many mechanical challenges, including the shear stress (SS) of blood flow, which render it prone to cell membrane ruptures. Such ruptures must be repaired efficiently to maintain cellular integrity and proper vascular function. However, whether SS of blood flow can indeed affect plasma membrane integrity of endothelial cells and whether any ruptures occurring are repaired is not understood. Here, we show that alterations in the SS of fluid flow induce membrane damage in human endothelial cells, and membrane ruptures increase with increasing shear alterations. Furthermore, we show that inherent SS disturbances at aortic branches in mice are associated with endothelial membrane wounds, which are not observed in regions of laminar flow. We also show that endothelial membrane damages inflicted by shear stress alterations are repaired by a Ca2+-dependent process that involves early endosome exocytosis to provide membrane material for wound closure, suggesting conserved and robust membrane repair responses to endothelial damage in vitro and in vivo. Thus, shear stress alterations, which frequently occur at sites of endothelial dysfunction and before associated pathophysiology, cause membrane wounds in the endothelium, which are repaired efficiently to maintain a functional vasculature.